APPLICATION OF ISLAMIC ECONOMIC VALUES IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) ON FOOD PRODUCTS IN MEKAR DAMAI VILLAGE, PRAYA DISTRICT, CENTRAL LOMBOK - Muhammad Rafi’i Sanjani; Naurun Nisa; L. M. Ikbal Patoni (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This research is motivated by the issue of Islamic values, such as honesty, cleanliness, responsibility, and khalalan, in micro, small, and medium enterprises, particularly in the food industry. Creating harmony will improve business performance. The aim of this study is to determine the understanding and application of Islamic economic values in small and medium micro enterprises in food products in Mekar Damai Village, Central Lombok. The research was conducted in Mekar Damai Village in the Praya District. It is a qualitative study, and the data sources are primary and secondary data obtained through interviews with informants and documentation at the research location. The study examines whether small and medium micro businesses in Mekar Damai Village adhere to Islamic values. Some business actors in Mekar Damai Village do not apply Islamic values, such as paying attention to the ingredients used to produce food. However, the village has implemented honest, friendly, clean, and halal attitudes well.